Maternal Risk Factors Associated with Preterm Birth: A Case Control Study - Gyamtsho, Sonam; Tenzin, Karma; Choeda, Tshering (Journal of Nepal Health Research Council, 2024)
Background: Preterm birth is the child birth before 37 completed weeks .Prematurity is one of the leading causes of neonatal morbidity and mortality due to the complications associated with it. The objective of the study was to determine the maternal risk factors associated with all preterm birth in singleton pregnancy at National hospital.Methods: Hospital based unmatched case control study was conducted between March 2021 to December 2021 at National hospital, Thimphu, Bhutan. Case to control ratio was 1:2.Data were collected using interviewer –administered structured questionnaires. The collected data were entered into Epi-data and exported into SPSS for analysis. Independent variables with p-valves<0.05 in the univariate analysis were entered to multi variable logistic model to estimate the strength of association .P-valve <0.05 was considered significant.Results: Total of 107 cases and 201 controls participated with a response rate of 95.95%.Multiple logistic regression showed that mothers with ANC follow ? four[aOR 9.58(7.36-28.86) ], previous history of preterm delivery [aOR 2.99(1.5-15.77) ], previous caesarean section [aOR 5.72(2.19-14.92)], prelabour rupture of membrane [aOR 8.67(3.78-19.73)], fetal growth restriction [aOR 7.28(2.11-25.11)] , and pre-eclampsia [aOR 10.99(6.75-85.29) were the risk factors positively associated with preterm birth .Conclusions: This study highlights that preeclampsia, number of antenatal care visits ? four, prelabour rupture of membrane, fetal growth restriction, previous caesarean section and previous preterm delivery were the risk factors for preterm birth. This show the need of early screening and prevention of preeclampsia, strengthening of antenatal care follow-up, and treatment of infection to prevent prelabour rupture of membrane, reducing primary caesarean section and more attention and care with previous preterm birth .Keywords: Case control study; preeclampsia; preterm birth; risk factors.